Educação popular e práticas extensionistas na cooperação no campo : a Associação de Cooperação Agrícola do Ceará (ACACE) em Canindé - Beserra, Raquel Carine Martins (2013)
The overall goal of the research was to study the relationship between popular education and the practices of technical assistance and rural extension professionals from Associação Agrícola do Ceará (ACACE), related to Movimento dos Sem Terra (MST) in the city of Canindé. The framework for an educational-dialogical proposal which is proper of the Popular Education in the field of agricultural extension is reflected by Paulo Freire in the late 1960s. The methodological approach was qualitative and discussions were used as a reference to approximate. The research used primary and secondary elements. With regard to the examination of the first, it was possible to choose two rural realities for the ATER monitoring activities: San Francisco das Chagas settlement and Terra Livre settlement. In these, there were selected some rural settled to be research subjects, as well as ATER professionals from ACACE. For both of them there were used Generator Groups, dynamics and semi-structured individual interviews. In addition to that, there were also direct observations and systematic recordings in field diaries. Also, MST militants, ATER coordinators from ACACE in Fortaleza, INCRA technicians and a NGO CACTUS professional; all were research subjects. To these, semi-structured individual interviews were applied. As to the examination of the secondary elements, it was performed the reading of ATER teams’ reports, of the reports of the process of expropriation of the respective settlements, of the nº. 02/2010 call of proposal of INCRA/CE and of the ATER technical proposal of the consortium ACACE ATER/CACTUS in Canindé. The results point to a contradictory reality. On one hand, the logic of productivity, the bureaucratic aspects and the absence of a specific training to work in an educational perspective limit the transformative actions of the local realities. Moreover, there is an effort to ensure that the ATER practices use discussing and participatory methodologies so the individuals can be part of a minimum educational process. However, by studying all the activities in the referred settlements, through the ATER policy, non-school education to young people and adults in the ATER field has been denied.